Combination of CRP and miRNA signature as a potential diagnostic strategy for Kawasaki disease - Huang, Xiaoyan; Li, Huiting; Zhao, Xiangrong; Zhang, Haixiang; Li, Yaping; Niu, Qian; Wang, Jiaojiao; Xu, Cuixiang (Frontiers in Pediatrics, 2025)
BackgroundKawasaki disease is the leading cause of acquired heart disease in children, yet timely diagnosis remains difficult due to overlapping symptoms with other febrile illnesses.MethodsIn a retrospective case–control study of 38 children with Kawasaki disease and 44 febrile controls, we measured hematological parameters and C-reactive protein (CRP) using standardized analyzers and profiled seven serum microRNAs by qRT-PCR. Biomarkers showing significant differences were used to build logistic regression models with a 70/30 train–test split, and diagnostic accuracy was assessed by receiver operating characteristic analysis. Functional enrichment of miRNA targets was explored using network analysis.ResultsCRP and three microRNAs (miR-223-3p, miR-19a-3p, miR-18a-5p) were significantly elevated in Kawasaki disease. Individually, these markers achieved strong discrimination (AUC: 0.846–0.986), while their combination yielded an AUC of 0.990, sensitivity 1.000, and specificity 0.923. The three microRNAs were positively correlated and enriched for pathways including p53 signaling and cell cycle regulation, with KCNQ1OT1 identified as a shared lncRNA interactor.ConclusionIntegrating CRP with a concise serum miRNA panel demonstrates promising discriminatory potential for Kawasaki disease vs. other febrile illnesses and suggests mechanistic involvement of p53-associated pathways, supporting future validation in larger, independent cohorts.